Avelumab (anti–PD-L1) as first-line switch-maintenance or second-line therapy in patients with advanced gastric or gastroesophageal junction cancer: phase 1b results from the JAVELIN Solid Tumor trial. Issue 1 (4th February 2019) - Chung, Hyun Cheol; Arkenau, Hendrik-Tobias; Lee, Jeeyun; Rha, Sun Young; Oh, Do-Youn; Wyrwicz, Lucjan; Kang, Yoon-Koo; Lee, Keun-Wook; Infante, Jeffrey R.; Lee, Sung Sook; Kemeny, Margaret; Keilholz, Ulrich; et al.
Abstract : Background: We evaluated the antitumor activity and safety of avelumab, a human anti–PD-L1 IgG1 antibody, as first-line switch-maintenance (1 L-mn) or second-line (2 L) treatment in patients with advanced gastric/gastroesophageal cancer (GC/GEJC) previously treated with chemotherapy. Methods: In a phase 1b expansion cohort, patients without (1 L-mn) or with (2 L) disease progression following first-line chemotherapy for advanced GC/GEJC received avelumab 10 mg/kg intravenously every 2 weeks. Endpoints included best overall response, progression-free survival (PFS), overall survival (OS), and safety. Results: Overall, 150 patients were enrolled (1 L-mn, n = 90; 2 L, n = 60) and median follow-up in the 1 L-mn and 2 L subgroups was 36.0 and 33.7 months, respectively. The confirmed objective response rate was 6.7% in both subgroups (95% CI, 2.5–13.9% and 1.8–16.2%, respectively), including complete responses in 2.2% of the 1 L-mn subgroup ( n = 2). In the 1 L-mn and 2 L subgroups, median duration of response was 21.4 months (95% CI, 4.0–not estimable) and 3.5 months (95% CI, 2.8–8.3) and disease control rates were 56.7 and 28.3%, respectively. Median PFS in the 1 L-mn and 2 L subgroups was 2.8 months (95% CI, 2.3–4.1) and 1.4 months (95% CI, 1.3–1.5), with 6-month PFS rates of 23.0% (95% CI, 14.7–32.4%) and 7.9% (95% CI, 2.6–17.2%), and median OS was 11.1 months (95% CI, 8.9–13.7) and 6.6 months (95% CI, 5.4–9.4), respectively. In the 1 L-mn subgroup, median OS measured from start of 1 L chemotherapy was 18.7 months (95% CI, 15.4–20.6). Across both subgroups, 20.7% had an infusion-related reaction of any grade. Other common treatment-related adverse events (TRAEs) of any grade included fatigue (10.0%) and nausea (6.7%). Treatment-related serious adverse events occurred in 4.0% of patients. Overall, 8.7% had a grade ≥3 TRAE, including 1 treatment-related death. Conclusion: Avelumab showed clinical activity and an acceptable safety profile in patients with GC/GEJC. Trial registration: ClinicalTrials.gov NCT01772004 ; registered 21 January 2013.